A CO2‐Tolerant Perovskite Oxide with High Oxide Ion and Electronic Conductivity. Issue 4 (1st December 2019) - Li, Ming; Niu, Hongjun; Druce, John; Téllez, Helena; Ishihara, Tatsumi; Kilner, John A.; Gasparyan, Hripsime; Pitcher, Michael J.; Xu, Wen; Shin, J. Felix; Daniels, Luke M.; Jones, Leanne A. H.; et al.
Abstract: Mixed ionic–electronic conductors (MIECs) that display high oxide ion conductivity (σo ) and electronic conductivity (σe ) constitute an important family of electrocatalysts for a variety of applications including fuel cells and oxygen separation membranes. Often MIECs exhibit sufficient σe but inadequate σo . It has been a long‐standing challenge to develop MIECs with both high σo and stability under device operation conditions. For example, the well‐known perovskite oxide Ba0.5 Sr0.5 Co0.8 Fe0.2 O3− δ (BSCF) exhibits exceptional σo and electrocatalytic activity. The reactivity of BSCF with CO2, however, limits its use in practical applications. Here, the perovskite oxide Bi0.15 Sr0.85 Co0.8 Fe0.2 O3− δ (BiSCF) is shown to exhibit not only exceptional bulk transport properties, with a σo among the highest for known MIECs, but also high CO2 tolerance. When used as an oxygen separation membrane, BiSCF displays high oxygen permeability comparable to that of BSCF and much higher stability under CO2 . The combination of high oxide transport properties and CO2 tolerance in a single‐phase MIEC gives BiSCF a significant advantage over existing MIECs for practical applications. Abstract : A single‐phase mixed ionic–electronic conductor (MIEC) based on the perovskite oxide Bi0.15 Sr0.85 Co0.8 Fe0.2 O3− δ (BiSCF) combines exceptional bulk transport properties, displaying an oxide ion conductivity among the highest for known MIECs, with high CO2 tolerance, which gives BiSCF a significant advantage over existing MIECs such as the well‐known Ba0.5 Sr0.5 Co0.8 Fe0.2 O3− δ for practical applications.